Kasus Mutilasi Dan Pengecoran Mayat di Tembalang Semarang Studi Putusan Nomor (528/pid.B/2023/PN smg) - Muhammad Rifai; M Harun; Riza Febriani (Jurnal Interpretasi Hukum, 2025)
This study discusses criminal liability for perpetrators of murder accompanied by mutilation and corpse encasement, focusing on Decision Number 528/Pid.B/2023/PN Smg. The main issue in this research is the absence of explicit regulation on mutilation in the Indonesian Penal Code (KUHP), causing such acts to be classified under murder provisions, particularly Articles 338, 339, or 340 of the KUHP. The objective of this study is to analyze how Indonesian criminal law constructs criminal responsibility in complex murder cases involving post-crime acts such as mutilation and concealment. This research uses a normative legal method with a qualitative approach through literature review. The findings show that in this case, the judge did not regard mutilation as a standalone crime but as part of a murder preceded or accompanied by another criminal act under Article 339 of the KUHP. Although the defendant mutilated and encased the victim’s body to cover up the crime, the element of premeditation required by Article 340 was considered absent due to the lack of a calm and calculated plan. Consequently, the defendant was sentenced to 20 years in prison. This research highlights the need for reform in Indonesia’s penal law to adequately respond to the complexity of modern criminal behavior.